EISELIANA Y HEODA, GENEROS ALTO ANDINOS Y AUSTRALES DE EUMAEINI NEOTROPICALES (LEPIDOPTERA: LYCAENIDAE) - Johnson, Kurt; Miller, Lee D.; Herrera G., José (Acta Entomológica Chilena, 2022)
Genera Eiseliana Ajmat de Toledo 1978 and Heoda Johnson, Miller & Herrera 1992 are revised to inelude two clades of species reslricled to high Andean and austral distributions in South America. A Key distinguishes Eiseliana and Heoda from taxa of thc pan-Neotropical Strymon eurytulus (Hübner) complex, somewhat similar in under surface wing pattern . Eiseliana and Heoda belong to a large worldwide clade of unrevised Eumaeini including species rich Strymon Hübner and may eventually be considered subgeneric high montane and austral lineages of Strymon. Formerly monotopic Eiseliana is expanded to inelude six species with differential occurrence of male forewing androconia ("brands") and brown or orange upper surface wing coloration but shared under surface pattern and slructural characters. As such, Eiseliana ineludes the widely distributed, polymorphic, "Thecla bicolor complex" of Southern South America along with other species occurring northward to Perú. Type species E. koehleri Ajmat de Toledo is synonymized with Thecla pnnona Clench 1944 and Eiseliana divided into two subclades: (1) brown species punona (Perú to Argentina), flavaria Uruta 1956 (Chile) (transferred from Thecla), new species patagoniensis (Patagonia) (all lacking forewing brands) and new species ollantaitamba (Perú) (with forewing brands); (2) orange and brown species bicolor Phillipi 1859 (júnior synonym Thecla quadrimaculata Hewitson 1874; "forms" leptocosma Hayward 1949 and tricolor Ureta 1949) (Chile to Patagonia) and new species probabila (Coquimbo Deserl and Central Valley biotic provinces, Chile, distinguished from continuous variation in the bicolor complex). Heoda ineludes type species heodes Druce 1909 (Perú), wagenknechti Ureta 1947 (Chile) (bolh transferred from Thecla) and new species colombiana (Colombia), suprema and nivea (both Patagonia). A lectotype is designaled for Thecla heodes. All Heoda species have inale forewing brands; the genus exhibits a unique integumental morphology. Biogeographical significance in the geographic distributions of Eiseliana and Heoda in discussed.